2005
DOI: 10.1142/s0256767905000795
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Zhi-quan Shen

Abstract: The studies of our group on the catalytic activities of rare earth calixarene complexes in polymer syntheses are reviewed. Rare earth calixarene complexes are effect catalysts for the polymerizations of butadiene, isoprene, ethylene, styrene, propylene oxide, styrene oxide, trimethylene carbonate and 2,2-dimethyl-trimethylene carbonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…The test functions are used to ensure that the differential equation and perhaps some boundary conditions are satisfied as closely as possible by the truncated series expansion. This is achieved by minimizing the residual function that is produced by using the truncated expansion instead of the exact solution with respect to a suitable norm [1,2,3,4,5,6,7,8,9, 10].…”
Section: Spectral Methodsmentioning
confidence: 99%
“…The test functions are used to ensure that the differential equation and perhaps some boundary conditions are satisfied as closely as possible by the truncated series expansion. This is achieved by minimizing the residual function that is produced by using the truncated expansion instead of the exact solution with respect to a suitable norm [1,2,3,4,5,6,7,8,9, 10].…”
Section: Spectral Methodsmentioning
confidence: 99%
“…An EDTA complex-titration of C6Sc revealed that the content of scandium in the calixarene complex was 2.75%, which indicates that every six phenol units of the p-tert-butylcalix [6]arene have 2.0 OH groups that coordinate to the scandium atom (Scheme 6), which differs from other rare earth p-tert-butyl calix [6]arene complexes. This is probably due to the weaker coordination capacity of the scandium atom.…”
Section: Ring-opening Polymerization Of Cyclic Carbonatesmentioning
confidence: 99%
“…A scandium p-tert-butylcalix [6]arene complex (C6Sc) has been synthesized from scandium isopropoxide and p-tert-butylcalix [6]arene. An EDTA complex-titration of C6Sc revealed that the content of scandium in the calixarene complex was 2.75%, which indicates that every six phenol units of the p-tert-butylcalix [6]arene have 2.0 OH groups that coordinate to the scandium atom (Scheme 6), which differs from other rare earth p-tert-butyl calix [6]arene complexes.…”
Section: Ring-opening Polymerization Of Cyclic Carbonatesmentioning
confidence: 99%
See 2 more Smart Citations